THEMIS and PTPRK in celiac intestinal mucosa: coexpression in disease and after in vitro gliadin challenge - Bondar, Constanza María (2014)
Celiac disease (CD) is an immune mediated, polygenic disorder, where HLA-DQ2/DQ8 alleles contribute around 35% to genetic risk, but several other genes are also involved. Genome-wide association studies (GWASs) and the more recent immunochip genotyping projects have fine-mapped 39 regions of genetic susceptibility to the disease, most of which harbor candidate genes that could participate in this disease process. We focused our attention to the GWAS peak on chr6: 127.99–128.38 Mb, a region including two genes, thymocyte-expressed molecule involved in selection (THEMIS) and protein tyrosine phosphatase, receptor type, kappa (PTPRK), both of which have immune-related functions. The aim of this work was to evaluate the expression levels of these two genes in duodenal mucosa of active and treated CD patients and in controls, and to determine whether SNPs (rs802734, rs55743914, rs72975916, rs10484718 and rs9491896) associated with CD have any influence on gene expression. THEMIS showed higher expression in active CD compared with treated patients and controls, whereas PTPRK showed lower expression. Our study confirmed the association of this region with CD in our population, but only the genotype of rs802734 showed some influence in the expression of THEMIS. On the other hand, we found a significant positive correlation between THEMIS and PTPRK mRNA levels in CD patients but not in controls. Our results suggest a possible role for both candidate genes in CD pathogenesis and the existence of complex, regulatory relationships that reside in the vast non-coding, functional intergenic regions of the genome. Further investigation is needed to clarify the impact of the disease-associated SNPs on gene function.